Peningkatan Kepedulian Masyarakat Sebagai Upaya Mewujudkan 2024 Zero Stunting di Kelurahan Punggawan, Kota Surakarta - Arinta Sekar Raihana; Dicky Julhan Kusuma; Annisa Tri Nabela; Nanda Ayu Safitri; Alfina Nur Hasanah; Intan Jayanti; Amandha Tito Nursahid; Prestiyana Kusuma Wardani; Andya Novelita Ayudianti; Rizka Noer Aziza; Tya Resta Fitriana (Edumedia Solution, 2022)
Stunting is a state of malnutrition associated with insufficient nutrition in children. Stunting can occur when the fetus is still in the womb and will appear when the child is two years old. This problem is a priority for the community and the government nationally because stunting can affect children's physical and cognitive development. Based on the stunting problem, our group carried out activities aimed at overcoming and preventing the occurrence of stunting status in the punggawan village, Surakarta. These activities included stunting socialization to posyandu cadres, make stunting education houses, provision of diarrhea corners, stunting prevention posts, and provision of additional food for toddlers at posyandu. In connection with the work program, it is hoped that the community and cadres more attention and care about stunting cases, and the Indonesia zero stunting program can success.